MENAKAR ADOPSI CLOUD-BASED ACCOUNTING PADA USAHA MIKRO, KECIL, DAN MENENGAH DENGAN COMPUTER SELF-EFFICACY, COMPUTER ANXIETY DAN PERCEIVED ENJOYMENT SEBAGAI FAKTOR DETERMINAN - Gusi Putu Lestara Permana; I Gusti Kadek Anggiriska Dwiyanti (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
Small and medium enterprises (SMEs) play a role in contributing to transformation in the better quadrant. SMEs have a positive effect on society and the economy because of their strategic value. SMEs use the simple financial record method, which can affect the decision-making process. Lack of ability in record keeping and financial management become a big issue. Implementing cloud accounting software is a way to reduce problems for SMEs due to the need to record their financial transactions. But not all SMEs use that software. This research conducted in Denpasar and involved 90 respondents. All the data analyzed with SPSS 24.0. The results found that each computer self-efficacy and perceived enjoyment had a positive and significant effect on behavioral intention, meanwhile computer anxiety had a negative and significant effect on behavioral intention to adopt cloud-based accounting in MSMEs